2007
DOI: 10.1080/02713680601187951
|View full text |Cite
|
Sign up to set email alerts
|

Oxysterols Induced Inflammation and Oxidation in Primary Porcine Retinal Pigment Epithelial Cells

Abstract: We conclude that in confluent primary porcine RPE cells, 24-hydroxycholesterol, 25-hydroxycholesterol, and 7-ketocholesterol are potent inducers of oxidation and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 43 publications
1
48
0
Order By: Relevance
“…The addition of exogenous cytochrome c and ATP to a cell-free system also resulted in cleavage of caspase-3 and -9 in extracts of U937 but not ARPE19 cells ( 122 ). Similarly, when ARPE19 cells were subjected to VEGF and IL-8 ( 8,9 ). However, the pathway by which these cytokines are induced does not seem to involve ROS ( 8, 9, 100 , 101 ).…”
Section: -Ketocholesterol In Chronic Infl Ammation and Agingmentioning
confidence: 99%
“…The addition of exogenous cytochrome c and ATP to a cell-free system also resulted in cleavage of caspase-3 and -9 in extracts of U937 but not ARPE19 cells ( 122 ). Similarly, when ARPE19 cells were subjected to VEGF and IL-8 ( 8,9 ). However, the pathway by which these cytokines are induced does not seem to involve ROS ( 8, 9, 100 , 101 ).…”
Section: -Ketocholesterol In Chronic Infl Ammation and Agingmentioning
confidence: 99%
“…Additionally, 24-OH significantly induces ROS production determined in primary porcine retinal pigment epithelial cells. (Joffre et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, some reports indicate that oxysterol influences proinflammatory properties (Wang N et al, 1996;Liu Y et al, 1997). Joffre et al reported that 7KCHO enhanced interleukin-8 gene expression using porcine retinal pigment epithelial cells (Joffre C et al, 2007). Interleukin-8 is a proinflammatory and chemotactic cytokine which might play a crucial role in the recruitment of monocytes and T lymphocytes into the arterial subendothelial space, consequently, promoting atherosclerotic lesion (Terkeltaub R et al, 1998).…”
Section: Discussionmentioning
confidence: 99%